Kewarganegaraan Global Dan Modal Sosial: Trust Dan Norms Dalam Pembentukan Karakter Santri Di Era Globalisasi - Wahono, Margi; Dasim Budimansyah; Elly Malihah; Susan Fitriasari; fegianowulung@gmail.com (Jurnal Civic Hukum, 2024)
The main focus of the research is how global citizenship interacts with social capital, especially elements of mutual trust and attachment to norms, in shaping the character of students amidst the impact of globalization. The research aims to understand how social capital strengthens attitudes of mutual trust and compliance with norms, as well as its contribution to the formation of adaptive and resilient students' character. A qualitative approach using the case study method was used to collect data through in-depth interviews, participant observation and document analysis at the Pondok Buntet Islamic Boarding School. Research findings show that social capital, especially beliefs and norms, plays an important role in shaping the character of students. The attitude of mutual trust between students and Islamic boarding school caregivers (trust) strengthens solidarity and social support, while compliance with Islamic boarding school norms (norms) helps students maintain moral integrity amidst the challenges of globalization. From this research, it is said to provide suggestions for Islamic boarding schools to emphasize the need to strengthen social capital to overcome the negative impacts of globalization and recommend development practices that strengthen beliefs and norms while still maintaining traditional values. Further research is recommended to explore other elements of social capital in educational contexts).